2021
DOI: 10.21037/atm-21-4332
|View full text |Cite
|
Sign up to set email alerts
|

Klotho upregulates the interaction between RANK and TRAF6 to facilitate RANKL-induced osteoclastogenesis via the NF-κB signaling pathway

et al.

Abstract: Background: α-Klotho (Klotho) plays a wide range of roles in pathophysiological processes, such as lowturnover osteoporosis observed in klotho mutant mice (kl/kl mice). However, the precise function and underlying mechanism of klotho during osteoclastogenesis are not fully understood. Here, we investigated the effects of klotho on osteoclastogenesis induced by receptor activator of nuclear factor kappa-B ligand (RANKL). Methods:The effects of klotho deficiency on osteoclastogenesis were explored using kl/kl mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This indicates that the decreased bone resorption observed in mutants is the direct result of the functional deletion of Klotho in Osx + -mesenchymal progenitors. Although osteoclast-specific Klotho also promoted Rankl-induced osteoclastogenesis, 26 OsxCre;KL fl/fl mice had conditional ablation of Klotho in Osx + -progenitors but not in osteoclasts, suggesting that Klotho is involved in osteoblast-dependent bone resorption, at least in part, by the regulation of Rankl in osteoblasts. It has been suggested that in bone marrow mesenchymal stem cells, RANKL binding to RANK activates RANKL signaling, which negatively regulates osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the decreased bone resorption observed in mutants is the direct result of the functional deletion of Klotho in Osx + -mesenchymal progenitors. Although osteoclast-specific Klotho also promoted Rankl-induced osteoclastogenesis, 26 OsxCre;KL fl/fl mice had conditional ablation of Klotho in Osx + -progenitors but not in osteoclasts, suggesting that Klotho is involved in osteoblast-dependent bone resorption, at least in part, by the regulation of Rankl in osteoblasts. It has been suggested that in bone marrow mesenchymal stem cells, RANKL binding to RANK activates RANKL signaling, which negatively regulates osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype is similar to that of Klotho-hypomorphic mice, which exhibited reduced osteoblast and osteoclast numbers and lower cortical bone thickness. 22 , 26 Moreover, deletion of Klotho in long bone mesenchymal stem cells ( Prx1Cre;KL fl/fl ), as well as in osteocytes ( Dmp1Cre;KL fl/fl ), both showed a trend towards reduced osteoclastic resorption parameters. 11 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…This process induces the formation of osteoclasts and promotes bone destruction. Therefore, TRAF6 plays a crucial role in osteoclast formation (Yu et al 2021 ). The Hedgehog (Hh) signaling molecule promotes osteoclast differentiation by facilitating the cis-activation of TRAF6 and stabilizing TRAF6 protein.…”
Section: The Rankl/rank Signaling Pathway Activates Nfatc1mentioning
confidence: 99%